The Head Shake Sensory Organization Test (HS-SOT): Normative Data and Correlation with Dynamic Visual Acuity Testing - Andrea E. Cripps; Scott C. Livingston (Bowling Green State University, 2017)
Background: Among healthy (asymptomatic) subjects and patients, the relationship between performance on the Head Shake Sensory Organization Test (HS-SOT) and performance on the Dynamic Visual Acuity (DVA) testing has not been reported. The purpose of this study was to establish normative data for the HS-SOT and compare performance on the HS-SOT and the DVA test. Hypothesis: A strong positive correlation would exist between the DVA and the HS-SOT. Study Design: A cross-sectional design was used. Level of Evidence: Level 3. Methods: Sixty asymptomatic subjects (34 females, 26 males, ages 20 to 26 years, 23.7±1.6) participated. Each subject's dynamic balance and visual acuity were assessed using the HS-SOT and DVA testing on the NeuroCom Balance System per manufacturer's protocol. Results: Equilibrium scores for the HS-SOT condition 2 (eyes closed, fixed surface) = 93.23±1.99, 95% CI = 92.7-93.8; and condition 5 (eyes closed, sway-referenced surface) = 66.69±1.13, 95% CI=64.4-70.0. The equilibrium score ratio (ESR) for condition 2 = 1.01±.003 (δ2=.001), and condition 5 = .94±.03 (δ2=.055). ESR fixed surface was negatively correlated with DVA loss symmetry % [R= - .36, p=.004, R2=.13] and with DVA errors (right) [R=-.30, p=.02, R2=.09]. Conclusion: Subjects demonstrated good dynamic postural stability on the HS-SOT and had minimal loss in their ability to maintain visual acuity during head movements. Clinical Relevance: Clinically derived HS-SOT data can be compared to normative data to assist the clinician with accurate assessment of postural instability.